Resilience of Covid-19 Survival Review from Optimism and Social Support - Prasetyaningrum, Juliani; Imadanty, Aqilah Larasati (Prosiding University Research Colloquium, 2022)
Covid-19 survivors are individuals who have been exposed to Covid-19 and managed to recover. Individuals who have been exposed to the Covid 19 virus is not an easy thing to live. Being a Covid-19 survivor does not only have an impact on their physical condition, but also on their mental health and quality of life. Resilience is the key to being able to get through the psychological suffering that has plagued Covid-19 survivors and return to normal life. This study aims to: 1) Determine the relationship between optimism and social support with resilience in covid survivors; 2) Knowing the relationship between optimism and resilience in covid survivors; and 3) Knowing the relationship between social support and resilience in covid survivors. The population of this research is active students of Muhammadiyah University of Surakarta who have contracted the Covid-19 virus and have recovered (survivors), aged 18-25 years. Data collection tools used are resilience scale, optimism scale, and social support scale. The data analysis technique used is Multiple Linear Regression. The results of data analysis show that the major hypothesis is accepted, that is, there is a significant relationship between optimism and social support and resilience. Minor hypotheses are also accepted, namely, (1) There is a positive relationship between optimism and resilience; and (2) There is a positive relationship between social support and resilience. This means that the more optimistic and the better of social support, the higher the resilience ability. The contribution of the independent variable to the dependent variable is 46.1%. The optimism variable contributed 22.5% and the social support variable contributed 23.6% to resilience. Meanwhile, 53.1% is influenced by other variables, such as: intellectual capacity, self-efficacy, self-concept and emotion regulation.